Cryo-EM structure of cardiac amyloid fibrils from an immunoglobulin light chain AL amyloidosis patient - Paolo Swuec (Nature Portfolio, 2019)
Immunoglobulin Light Chain Amyloidosis (AL) is the most common systemic amyloidosis occurring in Western countries. Here the authors present the 4.0 Å cryo-EM structure of light chain AL55 fibrils that were isolated from the heart of an AL systemic amyloidosis patient.